2018
DOI: 10.1111/mcn.12732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal obesity and breastfeeding intention on lactation intensity and duration

Abstract: Exclusive breastfeeding (EBF) has numerous maternal health benefits. However, EBF rates are lower in mothers with obesity. We sought to better understand whether maternal body composition measurements in early pregnancy are also predictive of lower rates of EBF. Healthy pregnant women with prepregnancy body mass index (BMI) of 17.5-51 kg/m 2 underwent determination of percent body fat (% body fat) in early (12-16 weeks) and late (37 weeks) gestation. Intent and duration of EBF were determined by surveys comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 44 publications
5
40
1
4
Order By: Relevance
“…When antenatal intentions were comparable between obese and non‐obese women, rates of breastfeeding initiation and duration were previously observed to be significantly lower among women with a prepregnancy BMI ≥30 kg/m 2 (Babendure et al, ; Lyons et al, ; Marshall, Lau, Purnell, & Thornburg, ). In this study, no differences in feeding practices were recorded in the early postnatal period, suggesting that variation in practices may only emerge over time.…”
Section: Discussionmentioning
confidence: 98%
“…When antenatal intentions were comparable between obese and non‐obese women, rates of breastfeeding initiation and duration were previously observed to be significantly lower among women with a prepregnancy BMI ≥30 kg/m 2 (Babendure et al, ; Lyons et al, ; Marshall, Lau, Purnell, & Thornburg, ). In this study, no differences in feeding practices were recorded in the early postnatal period, suggesting that variation in practices may only emerge over time.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-nine studies [16,60,[65][66][67]70,73,74,[76][77][78][79]83,86,88,89,[96][97][98][99][104][105][106][107][110][111][112]114,118]…”
Section: Study Characterisicsmentioning
confidence: 99%
“…T overall OR of being obese was significant (OR 1.47, 95% CI: 1.16-1.86) among 18 studies [7 73,75,80,85,91-93,96,97,101,103,109-111,113,117] but heterogeneity was substantial (I 2 = 93%, p for < 0.001,Tau 2 = 0.20). The subgroup analyses showed that the pooled risk among seven studies with higher quality score [71,73,96,97,[101][102][103][104][105][106][107][108][109][110][111] Table 3 shows the pooled risk for ABF cessation with 95% CI, heterogeneity, and publication bias and Figure 3 shows a forest plot for ABF cessation according to BMI categories. For studies that investigated underweight mothers, both the overall HR of four studies [70,76,102,115] (1.28, 95% CI: 0.71-2.31; I 2 = 95%, p for Q = 0.024, Tau 2 = 0.32) and the OR of 10 studies [69,71,73,92,96,97,101,103,109,116] (0.91, 95% CI: 0.64-1.28; I 2 = 86%, p for Q = 0.002, Tau 2 = 0.19) were insignificant.…”
Section: Study Characterisicsmentioning
confidence: 99%
“…Despite the associated health benefits, only 43% of infants are exclusively breastfed during the first 6 months worldwide, and in 2015 this percentage was 36% in Colombia [22]. Breastfeeding initiation and duration are even lower in overweight women; those with pre-pregnancy BMI ≥ 30 kg/m 2 are less likely to intend to exclusively breastfeed compared with normal weight and overweight women (78.8% vs 95.5 and 96.2%, respectively) [23]; whilst overweight women have significantly lower initiation and duration of breastfeeding than women in the normal range [24].…”
Section: Introductionmentioning
confidence: 99%